2022
DOI: 10.1007/s41999-022-00616-6
|View full text |Cite
|
Sign up to set email alerts
|

Upper versus lower body resistance exercise with elastic bands: effects on cognitive and physical function of institutionalized older adults

Abstract: Purpose To compare the effects of upper versus the lower-body resistance exercise on cognitive and physical functions of institutionalized older people. Methods This was a non-randomized multi-center comparative and crossover study (clincialtrials.gov code NCT03831373). Two experimental groups performed a 12-week intervention of resistance exercises with low-intensity elastic bands, one program focused on exercises of the upper body (n = 20, mean age 87.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…There were also significant improvements in "single left leg" and "single right leg" stands, showing improved balance in the older adults. These findings were consistent with those of many other studies [99][100][101][102][103][104], also showing that improved lower extremity strength leads to neurological integrity and reduces the risk of fall in older adults. In addition, from the perspective of older adults' adherence to exercise, after the implementation of the multi-component exercise pro-gram, it was found that the variety of exercises intrinsically motivated older adults to exercise, and the attendance rates of males and females reached 95% and 97%, respectively, demonstrating their exercise adherence [50,51].…”
Section: Discussionsupporting
confidence: 92%
“…There were also significant improvements in "single left leg" and "single right leg" stands, showing improved balance in the older adults. These findings were consistent with those of many other studies [99][100][101][102][103][104], also showing that improved lower extremity strength leads to neurological integrity and reduces the risk of fall in older adults. In addition, from the perspective of older adults' adherence to exercise, after the implementation of the multi-component exercise pro-gram, it was found that the variety of exercises intrinsically motivated older adults to exercise, and the attendance rates of males and females reached 95% and 97%, respectively, demonstrating their exercise adherence [50,51].…”
Section: Discussionsupporting
confidence: 92%
“…Table 1 presents the key characteristics of the included studies. Most were published between 2013 and 2022, and the majority were quantitative studies, including 7 quantitative non-randomized studies [ 42 , 46 , 48 , 54 , 58 , 65 , 66 ], 1 quantitative descriptive study [ 39 ], and 17 quantitative randomized controlled trials [ 40 , 41 , 43 45 , 47 , 49 53 , 59 64 ]. The subjects were all 60 or older; six of the studies looked specifically at older women [ 41 , 51 , 52 , 60 , 64 , 65 ], and one specifically at older men [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the 25 quantitative studies measured the effects of elastic band resistance training on upper and lower limb flexibility in older adults. Six were randomized controlled trials [ 40 , 44 , 50 , 52 , 53 , 64 ], five were non-randomized controlled trials [ 46 , 48 , 54 , 58 , 66 ], and one was a quantitative descriptive study [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations